2012
DOI: 10.1371/journal.pone.0036711
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Low-Dose Bisphenol A Targets in Human Foreskin Fibroblast Cells Derived from Hypospadias Patients

Abstract: Background/PurposeThe effect of low-dose bisphenol A (BPA) exposure on human reproductive health is still controversial. To better understand the molecular basis of the effect of BPA on human reproductive health, a genome-wide screen was performed using human foreskin fibroblast cells (hFFCs) derived from child hypospadias (HS) patients to identify novel targets of low-dose BPA exposure.Methodology/Principal FindingsGene expression profiles of hFFCs were measured after exposure to 10 nM BPA, 0.01 nM 17β-estrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…We have recently identified that MMP11 is a novel target of low dose of BPA exposure and that BPA can inhibit MMP11 expression in a dose-dependent manner in hFFCs derived from child HS patients. Furthermore, we found that mRNA levels of MMP11 were significantly lower in the HS group compared with the control and CO groups suggesting that the involvement of BPA in the development of HS might be related with the downregulation of MMP11 [17]. The results of this study are in accord with this hypothesis.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We have recently identified that MMP11 is a novel target of low dose of BPA exposure and that BPA can inhibit MMP11 expression in a dose-dependent manner in hFFCs derived from child HS patients. Furthermore, we found that mRNA levels of MMP11 were significantly lower in the HS group compared with the control and CO groups suggesting that the involvement of BPA in the development of HS might be related with the downregulation of MMP11 [17]. The results of this study are in accord with this hypothesis.…”
Section: Discussionsupporting
confidence: 85%
“…BPA has been detected in 92% of urine samples in a US reference population, suggesting that humans might be continuously exposed to this compound in their daily lives [16]. To better understand the molecular basis of the effect of low-dose BPA exposure on human reproductive health, we previously performed a genome-wide screen using human foreskin fibroblast cells (hFFCs) derived from child HS patients to identify novel targets of low-dose BPA exposure [17]. We reported that the expression of matrix metalloproteinase-11 ( MMP11 ), a well-known effector of development and normal physiology, was downregulated by BPA in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arrays were scanned using a GenePix 4000B Microarray Scanner (Axon Instruments). Data normalization and analysis were performed with GeneSpring GX13.0 (Agilent Technologies) as previously described (27). All data are MIAME compliant, and the raw data were deposited in the Gene Expression Omnibus (www.ncbi.nlm.nih.gov/geo; accession no.…”
Section: Microarray Analysismentioning
confidence: 99%
“…The Ingenuity Pathway Analysis (IPA) program (Ingenuity Systems) was used to identify networks and canonical pathways associated with differentially expressed genes following ACR treatment as previously described (27).…”
Section: Network Generation and Pathway Analysismentioning
confidence: 99%